Las rutas del aprendizaje en la matemática y los juegos - Huarcaya Aliaga, Ruth (2014)
In this article, we develop one of thestrategies proposed by the Learningroutes for the knowledge of Numbersand Operations, aimed to the third cycleof Primary Education; the game, whichwe will detail to allow the teacher toadapt it or reproduce it in class.